Regulation of the NRG1/ErbB4 Pathway in the Intrinsic Cardiac Nervous System Is a Potential Treatment for Atrial Fibrillation - Zhou, Xiaoya; Wang, Zhuo; Huang, Bing; Yuan, Shenxu; Sheng, Xia; Yu, Lilei; Meng, Guannan; Wang, Yuhong; Po, Sunny S.; Jiang, Hong (Frontiers in Physiology, 2018)
Background: The NRG1/ErbB4 signaling mechanism has been widely studied in the central nervous system for many years. However, the role of this pathway in modulating the intrinsic cardiac nervous system is largely unknown. Objective: The present study investigated whether the NRG1/ErbB4 signaling system affects the activity of major atrial ganglionated plexi (GP) in a paroxysmal atrial fibrillation (AF) model by 6-h rapid atrial pacing (RAP). Methods: Twenty-four dogs were randomly divided into (1) a control group (saline microinjections into GP), (2) RAP group (saline microinjections into GP plus 6h-RAP), (3) NRG1 group (microinjections of neuregulin-1 into GP plus 6h-RAP) and (4) NRG1 + ERA group (microinjections of neuregulin-1 and ErbB4 receptor antagonist-ERA into GP plus 6h-RAP). The effective refractory period (ERP), window of vulnerability (WOV), anterior right GP (ARGP) function and neural activity were measured. ARGP tissues were excised for histological study and western blotting. Results: When compared to the control group, 6h-RAP produced a significant (1) decrease in ERP, an increase in ∑WOV, (2) an increase in ARGP neural activity and neural function, and (3) an increase in c-fos and nerve growth factor protein expression in the ARGP. However, microinjection of NRG1 into the ARGP prior to RAP prevented ERP shortening and AGRP activity enhancement and inhibited the expression of c-Fos and NGF proteins. Furthermore, these changes were significantly attenuated by pretreatment with an ErbB4 receptor antagonist. Conclusions: The NRG1/ErbB4 signaling pathway may exist in the GP, and activation of this pathway suppressed RAP-induced GP activation, atrial electrical remodeling and AF.